The SPK Penentuan Anggota Panitia Pemungutan Suara di Kabupaten Labuhabatu dengan Metode PSI - Has, Syahnila Natasya; Subagio, Selamat; Dalimunthe, Abdul Hakim (LPPM Universitas Al Washliyah Labuhanbatu, 2025)
The Decision Support System for Determining PPS Elections at the KPU Labuhanbatu Office, uses the PHP (Hypertext Preprocessor) Programming Language. This application system was created because there was a problem at the start of the election process so it is hoped that this SPK can assist the election process. Making a system of conducting observations and interviews with the school. The last stage of designing an application system is the stage of implementing a program that will produce an election application system program at the Labuhanbatu KPU Office. Computerized systems are very appropriate for processing data and producing useful information. The data that is input to this application system, namely, among other things, each criterion data in the election, while the output of this system will produce reports including the Election Result Report in Labuhanbatu Regency. With this system, the election results will be easily printed and stored and parties who need to be proof of results.Keywords: Decision support system